Fractal and Chaos Characteristics in Rock Milled Process - Xinxia CUI; Chenxu LUO (Institute of Advanced Engineering and Science, 2014)
In order to research the mechanism and to reveal the natural characteristics in rock milled process, the milling load was deemed to be a component of the deterministic nonlinear dissipation system. The characteristic factor model of milling load was built on the basis of time delay method, and the phase-space of milling load was rebuilt. the dimensional phase-type of broken attractor was described. The results indicated that the broken attractor was a fractal set ,which acquired through the scale conversion of phase-space developed by each dimension. The relevant dimension of broken attractor can be as the identification to reflect the change of rock broken mechanism. And the Lyapunov exponential spectrum and the maximum Lyapunov exponent were acquired by confirming the system reconstruction dimension. The chaos phenomenon was existed in the rock milled process, which provides the basis for building the deterministic model of rock milled process. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3448